Correlation for Photocatalytic Degradation Kinetics of Carboxylic Acids using Electrochemically Synthesized Al2S3 Nanoparticles and Study of Antibacterial Activity - Kumar, H.C. Charan; Shilpa, R.; Ananda, Sannaiah (Asian Journal of Chemistry, 2020)
Aluminium sulfide (Al2S3) nanoparticles were successfully synthesized by electrochemical method. Further, the synthesized nanoparticles were used as a photocatalyst for degradation of trichloroacetic acid, chloroacetic acid, acetic acid and degradation kinetics was studied by volumetric method using NaOH under various experimental conditions. The Al2S3 nanoparticles were characterized by UV-visible spectroscopy, X-ray diffraction and SEM-EDAX. The study of UV-visible spectroscopy indicates that Al2S3 nanoparticles shows maximum intensity peak at 222 nm in the UV region and there is no absorption peak in the visible region, therefore the synthesized nanoparticles is active under UV light and band gap energy was found to be 3.07 eV, which was calculated using Tauc plot. The structure of Al2S3 was found to be tetragonal structure and average crystal size was found to be 25.76 nm, which was calculated using Debye-Scherrer′s formula. The SEM results showed that Al2S3 appears as nanoflakes with agglomerated. The presence of aluminium and sulfur was confirmed using EDAX spectra. The photocatalytic activity of the synthesized Al2S3 nanoparticles was examined by taking three carboxylic acids by volumetric method. Taft LFER was tested, the isokinetic temperature β was calculated for oxidation of carboxylic acids. The antibacterial activity was investigated for synthesized nanoparticles by using Bacillus subtilis MTCC 2763 and Escherichia coli MTCC 40 of different bacteria.